Psychosocial factors influencing effective learning among Basotho learners during the COVID-19 pandemic in a rural high school - Mofokeng, M. M. (University of the Free State, 2023)
The learning process is built on decisions and constant assessments obtained from what is learned and how it is learned, the support given to access knowledge or concepts, and whether what is remembered by the learner is correct. However, this learning process was disrupted by the Corona virus disease 2019 (COVID-19) lockdown regulations that were put in place under the auspices of the World Health Organization, in order to curb the rapid spread of the COVID-19 pandemic. Also, the COVID-19 pandemic had an impact on teachers and learners’ mental health which prevented effective learning. The primary aim of this study was to explore the psychosocial factors that influenced effective learning among Basotho learners in a rural high school during the era of the COVID-19 pandemic. A literature review gave the background to an observed inquiry using a qualitative approach. Case study design was chosen for this study, since it permitted the researcher to explore the experiences of various stakeholders during the COVID-19 pandemic era of the Basotho learners within their real-world context and collect data on how they make sense of their experiences. A rural high school was purposively chosen as a research site, together with the four learners, four parents or guardians, four teachers, School Governing Body, School Based Support Team and School Management Team members. Data was generated through in-depth interviews and thoroughly analyzed. Narrative analysis was used to analyse the data collected through in-depth interviews. Data was organised through the use of thematic analysis. The study employed interpretivism paradigm. The Protection Motivation Theory and Self-Efficacy Theory constitute the theoretical frameworks of the study. The research concluded that psychosocial factors that influenced effective learning among Basotho learners in a rural high school during the COVID-19 pandemic era ranged from panic behaviour, or collective hysteria to pervasive feelings of hopelessness and desperation, which were associated with negative outcomes including suicidal behaviour. It also triggered a wide variety of psychological problems, such as panic disorder, anxiety, and depression which disturbed effective learning. The research also concluded that learners' reactions to the challenges they faced in the Thabo Mofutsanyana District rural high school and their strategies and remedies to the challenges show that they value teaching and learning. The learners' strategies and efforts to solve the challenges they faced during the COVID-19 pandemic in the rural high school also enhanced teaching and learning.
Dissertation (M.Ed. (Psychology of Education))--University of the Free State, 2023
Keywords: Psychosocial factors; Effective learning; Basotho learners; Rural high school; COVID-19 pandemic